Broadcast of Things - A Thought Experiment - Hartmann, Markus; Tröger, Hans-Martin; Kilian, Gerd; Robert, Jörg; Nowak, Thorsten; Heuberger, Albert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2014)
Sensor networks as well as the Internet of Things, are getting more and more popular in many numbers of applications. However, a bidirectional link between the individual nodes is not always needed and leads to higher costs and power consumption. This paper introduces the concept Broadcast of Things which reverses the well known broadcast architecture. It is shown that in realistic environments the proposed concept of broadcasting sensor nodes offers an interesting alternative to usual sensor networks. By simulations the efficiency benefits of broadcasting sensor nodes is illustrated. To give an idea about the capability of the broadcast concept, a 1 cm3 cubic demonstrator is shown. With a discussion and summary about the different efficiencies by the two concepts this paper is concluded. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.komele.broadc
Keywords: Broadcast of Things; efficiency; propagation model; sphere packing bound; wireless sensor networks

Efficient Power Supply for Telemetry Sensor Nodes - Tröger, Hans-Martin; Kilian, Gerd; Robert, Jörg; Hartmann, Markus; Nowak, Thorsten; Meyer, Manuel; Heuberger, Albert (IEEE Radio & Wireless Week, 2014)
Unidirectional telemetry systems for long range wireless data transmission are becoming more and more important for localization and sensor applications. A small size of the transmitter nodes, required for mobility, can only be reached by the use of tiny batteries. This paper explains, how an energy storage device like a capacitor can help to handle the current limitation of such batteries, e.g. coin cell batteries. Different circuits for the charge of the capacitor and for the power supply of sensor nodes are discussed. The efficiencies of the supply concepts are calculated and compared. The realizable number of transmissions for the different power concepts and a given type of battery is estimated. As a consequence of our calculations the optimal power concept could be implemented into our 1 cm3 cubic transmitter demonstrator, which is introduced in this paper. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.komele.effici
Keywords: coin cell battery; DCDC converter; efficiency; energy stor-age; LDO; telegram splitting; telemetry systems